Penilaian Kondisi Komunitas Mangrove di Kawasan Hutan Mangrove Ciletuh, Sukabumi, Jawa Barat - Muhammad Imran Zaelani; I Wayan Arthana; Gede Surya Indrawan (Journal of Marine Research and Technology, 2023)
This study aimed to analyze the composition of mangrove vegetation, the Important Value Index (IVI) of mangroves, the condition of the mangrove community (mangrove density and mangrove canopy cover), and environmental parameters as supporting data in the Ciletuh Mangrove Forest Area, Sukabumi, West Java. The research method used in this research is a quantitative descriptive method. The number of stations determined is four; each observation station is made of a plot of 10 x 10 meters, with three plots for each station. The results found seven mangrove species, namely Avicennia marina, Bruguierra cylindrica, Rhizophora apiculata, Rhizophora mucronata, Aegiceras corniculatum, Hibiscus tiliaceus, and Nypa fruticans. The mangrove species found were dominated by A. marina, where this species was found at all stations and had the highest Important Value Index (IVI) value among other species, ranging from 88.96 - 195.55%. Mangrove communities in the Ciletuh Mangrove Forest Area are in good condition referring to the Decree of the Minister of Environment No. 201 of 2004 concerning Standard Criteria and Guidelines for Mangrove Damage with density values ranging from 1533 – 2933 stands/ha and the percentage of mangrove canopy cover ranging from 80.54 - 82.22%.